Effect of Molecule Coverage on Nitric Oxide Reduction Reaction on Cu(111) (Communications in Computational Chemistry, 2025)
Electrochemical nitrogen oxide reduction reaction (NORR) can simultaneously remove atmosphericpollutant NO and produce the important chemical ammonia ($NH_3$), which, therefore, has garneredsignificant attention. However, the effect of molecule coverage on the catalyst surface on electrocatalyticactivity is less discussed. In combination with atomic ab initio thermodynamics and first-principlescalculations, the relationship between the NO coverage and catalytic NORR activity on Cu(111) isunraveled in this work. Results indicate that the adsorption stability and the limiting potential ($U_L$) ofNORR on Cu(111) is closely related to NO coverage. In the case of standard conditions (1 atm, 300 K),NO adsorption with a coverage of 1/4 monolayer (ML) is the most stable configuration, though thecorresponding $U_L$ (0.34 V) is higher than those of 1/9 (0.29 V) and 1/16 ML (0.29 V) adsorption whilesignificantly lower than that of 1 ML (0.78 V). Therefore, our study provides insights into the role oftemperature, pressure, and molecule coverage in electrochemical reactions.
Keywords: NORR; Cu(111); molecule coverage; first-principles calculations